Komunikasi Interpersonal Guru Dengan Orang Tua Dalam Membentuk Karakter Murid : (Studi Analisis: Madrasah Diniyah Raudlatul Mutaallimin Lembanah Waru Timur Waru Pamekasan) - Musleh Musleh; Ahmad Wahyudi; Ahsan Riadi (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2022)
The purpose of this study was to determine the interpersonal communication of teachers and parents in shaping the character of students and the impact of interpersonal communication between teachers and parents in shaping the character of students. The type of research is descriptive type with a qualitative approach. The data collection methods used were observation, interviews and documentation from several sources consisting of key informants, namely parents and teachers, main informants, namely students, and supporting informants, namely the head of the madrasa. Technical analysis used is data reduction, data presentation, and conclusion drawing/verification. The results of the study: (1) interpersonal communication between parents and teachers in shaping the character of students is fairly effective because of the implementation of effective interpersonal communication, openness, positive attitude, mutual support, and equality between teachers and parents. The interpersonal communication model is interactional through formal and non-formal communication. (2) The impact of interpersonal communication on the formation of student character, namely; (a) increase the attention and responsibility of teachers, (b) influence student attitudes and behavior, (c) build and maintain harmonious relationships.